Meningkatkan Hasil Belajar Lompat dan Loncat Melalui Permainan Tali Merdeka (Department of Physical Education, Sport, Health and Recreation, 2015)
Purpose of this study was to determine the increase in the ability to jump and jump in the fourth-grade students of SD Negeri 04 Rowosari Ulujami District of Pemalang in the school year 2013/2014 through independent learning through games ropes. This study uses a Class Action Research (PTK). Source of data in this study entire fourth-grade students of SD Negeri 04 Rowosari Ulujami Pemalang District of academic year 2013/2014. The subjects were fourth-grade students of SD Negeri 04 Rowosari Ulujami District of Pemalang in the school year 2013/2014 amounted to 27 students. The results obtained have implications for the development of the teaching of physical education in schools in general and especially in SD Negeri 04 Rowosari Ulujami District of Pemalang in the academic year 2013/2014